Robert Merle théoricien et praticien de la politique-fiction - Anne Wattel (ReS Futurae)
In the 70’s, in the midst of the Cold War, a literary genre, both disregarded and often described as "hybrid”, – political fiction – develops in Anglo-Saxon countries. Robert Merle is the first literary critic, theorist and practitioner of this genre in France. As he has just finished his novel The Day of the Dolphin, Merle lays out, in a special issue of Le Monde in October 1967, the golden rules of political fiction: a short-term anticipation which introduces one or several minor variables, a critical vision in keeping with a serious genre, which reveals and alerts against the planetary anguish that grips mankind in the second half of the twentieth century. But Merle’s political fiction differs from its American counterpart: it is based on scientific advance; it rejects all false and artificial optimism, all happy endings; and, first and foremost, it has a philosophical reach that makes it long-lasting.